Pusaka Saujana Dataran Tinggi Dieng Dampak Kegiatan Pariwisata dan Pertanian Terhadap Kemenerusan Pusaka Saujana di Dataran Tinggi Dieng - , ANGGA SURYA NUGRAHA, Prof. Bakti Setiawan ,MA,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of this research to review the cultural landscape of Dieng Plateau and to answer whether it can be regarded as a cultural landscape. There four aspects studied in this research 1) to describe the history of environmental, archaeological objects, and philosophy of life and culture of people in the Dieng Plateau 2) to describe the unique shape of cultural landscape Dieng Plateau 3) to evaluate the potential of cultural landscape Dieng Plateau 4) to evaluate the influence of tourism and agricultural activities to cultural landscape of Dieng Plateau. The research method in this research was descriptive research. Data are obtained from secondary data, interviews and observations. Based on the data obtained by both primary and secondary, data were then analyzed using qualitative and quantitative approaches. This study is able to describe the form of cultural landscape at the Dieng Plateau , there are land use pattern, the livelihood, local architecture, natural formations. Cultural landscape in Dieng Plateau can be categorized as unuique because it has a unique community, religious values, history and values of science, as well as land form of Dieng. Dieng Plateau can be said to be a cultural landscape where meet the criteria for a strong historical value, heritage resources, typical geographical conditions, while natural systems and the biophysical and socio-cultural changes are still ongoing. Cultural landscape of Dieng Plateau is getting threats from tourism and agricultural activities. Unfortunately, conservation efforts by local authorities have not been running optimally due to the ineffective planning, implementation, and evaluation of a program.